BOROJÓ (Borojoa patinoi): SOURCE OF POLYPHENOLS WITH ANTIMICROBIAL ACTIVITY - SOTELO D., Indira; CASAS F., Nidia; CAMELO M., Gustavo (Vitae, 2010)
According to popular belief, borojó (Borojoa patinoi cuatrec.) fruit is recognized for its preservative properties, possibly related to the presence of phenolic compounds. The content of polyphenols and their antimicrobial activity against pathogens as Escherichia coliand Staphylococcus aureus were evaluated in this research. Borojó fruit has polyphenol content between 600 and 800 mg gallic acid/100gr, and antimicrobial activity against S. aureus and E. coli with inhibition halos between 12 and 9 mm respectively. These results showed the advantages that have this fruit from the Rubiaceae family as a potential antimicrobial agent in food and cosmetics industries.